The Indirect Effects of Social Network Characteristics and Normative Beliefs in the Association between Adolescent Depressive Symptomatology and Binge Drinking. Issue 9 (2nd September 2017) - Harris, Michelle N.; Teasdale, Brent
ABSTRACT: Adolescents who experience depression have different attributional styles and may overestimate how much alcohol their friends consume. This misperception may increase binge drinking among adolescents with depressive symptomatology. The social networks of adolescents with depressive symptomatology are systematically different, providing different social learning opportunities. Using Add Health, we find that individuals who suffer from depressive symptomatology are more likely to have peers with higher depression scores. Adolescents with higher depressive symptomatology are more likely to perceive their peers as drinking alcohol. Our results suggest that normative beliefs are the key mediator in explaining the association between depressive symptomatology and binge drinking.